Pengaruh Sistem Pengendalian Internal, Karakteristik Personal, Kondisi Ekonomi, Besar Pinjaman, dan Nilai Jaminan terhadap Pengembalian Kredit pada PT. BPR Nusamba Rambipuji - Regina Tetisa Nur Amaniah; Dedy Wijaya Kusuma; Nurshadrina Kartika Sari (Institut Teknologi dan Sains Mandala, 2022)
Repayment of credit is the ability of prospective debtors to repay credit in accordance with the amount, schedule, and time period that has been determined. Not all debtors are able to return credit in accordance with the agreed agreement. At PT. BPR Nusamba Rambi Puji the rate of return on current loans fluctuated from year to year. The purpose of this study was to examine the effect of the internal control system, personal characteristics, economic conditions, loan size, and collateral value on loan repayment (PT. BPR Nusamba Rambi Puji). The independent variables used include: Internal Control System (X1) Personal Characteristics (X2) Economic Conditions (X3) Loan Size (X4) and Collateral Value (X5). The dependent variable is Credit Return (Y). The sample in this study were the credit employees of Pt. Bpr Nusamba Rambipuji selected through purposive sampling method. The analysis used is multiple linear regression analysis, F test, t test, and data quality test through validity and reliability tests. Simultaneously the results of the analysis show that all independent variables have an influence on credit repayments. Meanwhile, it is partially known that the internal control system and the size of the loan are variables that have an influence on credit repayment.